Identifikasi Cacat Produk Botol Plastik 500 ML dengan Pendekatan Metode FTA (Fault Tree Analysis) di PT. X Pasuruan - Abdul Wahid; Nuriyanto Nuriyanto; Misbach Munir; Adimas Syarifuddin (Universitas Merdeka Malang, 2023)
Â Â PT. X Pasuruan is a company engaged in the manufacture of plastic packaging. This industry is a job order industry that manages plastic pellets through the production process into a product that the customer wants. The formation of plastic products is carried out in two ways, namely blow molding, which is the process of processing plastic pellets into a product by blowing air into the plastic to be printed here. disabled. So that in this study the aim was to identify the factors that cause the biggest defects in 500 ml Plastic Bottle products using the FTA (Fault Tree Analysis) method so that 3 types of defects were produced with a total percentage, namely the Gross Material defect with a weight of 30%, the Gross Oil defect with a weight of 18%, and Folding defects with a weight of 15%, so that the main improvements are focused on these three types of defects and result in tighter material control, starting from the supplier until before the material enters the production process and is ready to stand by in cleaning the machine area regularly.Â PT. X Pasuruan merupakan industri yang bergerak di bidang manufaktur pembuatan kemasan plastik. Industri ini ialah industri job order yang mengelolah biji plastik lewat proses penciptaan jadi suatu produk di mau customer. Pembetukan produk plastik dicoba dengan 2 metode ialah blow moulding ialah proses pengolahan biji plastik jadi suatu produk dengan metode meniupkan hawa dalam plastik yang hendak di cetak di mari masih terjalin banyak hambatan salah satunya produk cacat yang menggapai 2% sehingga dibutuhkan identifiasi kasus yang terjalin pada produk cacat. Sehingga dalam riset ini tujuannya merupakan Mengenali aspek pemicu terbentuknya cacat terbanyak pada produk Botol Plastik 500 ml dengan tata cara FTA( Fault Tree Analysis) sehigga dihasilkan 3 tipe defect dengan total persentase ialah defect Kotor Material dengan bobot sebesar 30%, defect Kotor Oli dengan bobot sebesar 18%, serta defect Melipat dengan bobot sebesar 15%, sehingga revisi utama difokuskan pada ketiga tipe defect tersebut serta dihasilkan pengendalian material di perketat, mulai dari supplier hingga saat sebelum material tersebut masuk proses penciptaan serta siap siaga dalam mensterilkan zona mesin secara berkala.